To study the commonly used raw materials in Iron and Steel Industry - Rao, Lakkoju Sankara (IIT BHU, 2022)
To study the commonly used raw materials in Iron and Steel Industry. This video shows the tools used for Identification of different raw materials Iron making & Steel making raw materials (Hematite, Magnetite, Limonite, Sinter, Pellets, HBI, Coke, Limestone), Ferro Alloys(Fe-Mn, Fe-Cr), Nonferrous Metals and alloys, Fine Powders and Minerals and Ores PART 1 TOOLS USED FOR IDENTIFICATION&IDENTIFICATION OF MINERALS(00:00 to 13.54) PART 2 RAW MAERIALS USED IN IRON MAKING AND STEEL MAKING PART 3 NON-FERROUS METALS AND ALLOYS PART 4 FINE POWDER& MINERAL AND ORES
Keywords: FERROUS METALS AND ALLOYS; FINE POWDER& MINERAL AND ORES